Disaster planning, structural assessment, demolition and recycling : report of Task Force 2 of RILEM Technical Committee 121-DRG, Guidelines for Demolition and Reuse of Concrete and Masonry /: report of Task Force 2 of RILEM Technical Committee 121-DRG, Guidelines for Demolition and Reuse of Concrete and Masonry. ([2014?]) - Unknown
No abstract available